Utilization of Magnetic Mesoporous Silica (Fe3O4@mSiO2) in Adsorption, Loading, and Release Kinetics of Diphenhydramine Drug - Hussein, Enaas Abdul; Kareem, Sameer H.; Ali, Inaam H. (Iraqi Journal of Science, 2025)
The current study uses mesoporous silica magnetic Fe3O4@mSiO2 nanoparticles as core-shell materials to deliver the drug diphenhydramine (DPH). To investigate the DPH drug’s adsorption behavior in aqueous solutions, the batch approach has been employed. The adsorption evaluations that were obtained were fitted with the Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich isotherms models. According to the results, the Freundlich model was the best fit for the data, and the type of adsorption process used was physical. After kinetic analysis, it was discovered that the data agreed quite well with the pseudo-second-order kinetic equation. The Fe3O4@mSiO2 carrier’s DPH drug loading capacity and release kinetics were also examined. The calculated amount of DPH loaded on the sample was 13.33 mg drug/mg sample. The release profiles of the loaded Fe3O4@mSiO2 sample show that the DPH release percentage in the water and (phosphate buffer solution) PBS solution is 57.23 and 97.27%, respectively. The release kinetics was also studied using three models: Korsmeyer-Peppas, first-order kinetic release, and Kopcha. The results indicate that the Kopcha model conforms more closely to the data release than other models.